(untitled) (Research, Society and Development, 2022)
The chronic kidney disease is the main cause of kidney illness in dogs. The evaluation of glomerular filtration rate (GFR) is essential for the diagnosis of this disease, using endogenous or exogenous creatinine clearance tests. Two methods of evaluation can be found in Brazil, the dual twenty minutes, and the twenty-four hours one. Ten healthy (verified with hematological, urinalysis, biochemical and physical evaluation) animals with ages between one and eight years and weight around twelve kilograms from the kennel of veterinary hospital of Universidade de Franca was submitted to three kinds of GFR tests (twenty-four hours endogenous creatinine clearance, clearance of exogenous creatinine and four hour endogenous creatinine clearance). Significant difference was found between the results of the methods, indicating that the four-hour endogenous creatinine clearance has potential to be utilized in the veterinarian routine.